2015
DOI: 10.1021/acsnano.5b05138
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Human Epidermal Growth Factor Receptor 2 Degradation in Breast Cancer Cells by Lysosome-Targeting Gold Nanoconstructs

Abstract: This paper describes how gold nanoparticle nanoconstructs can enhance anti-cancer effects of lysosomal targeting aptamers in breast cancer cells. Nanoconstructs consisting of anti-HER2 aptamer (human epidermal growth factor receptor 2, HApt) densely grafted on gold nanostars (AuNS) first targeted HER2 and then were internalized via HER2-mediated endocytosis. As incubation time increased, the nanoconstruct complexes were found in vesicular structures, starting from early endosomes to lysosomes as visualized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
110
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(111 citation statements)
references
References 55 publications
1
110
0
Order By: Relevance
“…These results have inspired further research recently leading to combination with a nanocarrier to realize theranostic application. 57 These works showed the potential of aptamers as alternative therapeutics by their interactions with target biomarkers.…”
Section: Aptamer-based Molecular Recognition For Biomarker Targetingmentioning
confidence: 99%
“…These results have inspired further research recently leading to combination with a nanocarrier to realize theranostic application. 57 These works showed the potential of aptamers as alternative therapeutics by their interactions with target biomarkers.…”
Section: Aptamer-based Molecular Recognition For Biomarker Targetingmentioning
confidence: 99%
“…52 The trimeric version of the HApt used in this study was initially developed by Mahlknecht et al, 41 who demonstrated that HApt promoted translocation of HER2 from the cell surface to the cytoplasm in HER2-overexpressing N87 gastric cancer cells, which was associated with lysosomedependent clearance of HER2 protein. Lee et al 40 reported that HApt exerted a cytotoxic effect in HER2-overexpressing SKBR3 breast cancer cells. HApt has been shown to induce cross-linking of HER2 on the cell surface, resulting in the translocation of HER2 to cytoplasmic vesicles for lysosomal degradation.…”
Section: Discussionmentioning
confidence: 99%
“…HER2-negative control aptamer (NCApt) is a trimeric concatenation of a negative control oligonucleotide (5′-AGATTGCACTTACTATCT-3′). 40,41 high performance liquid chromatography-purified HApt, NCApt, and other oligonucleotides (between 20 and 100 nt) (Table 1) were commercially synthesized (Sangon Biotech Co., Ltd., Shanghai, People's Republic of China). The dye Texas red was conjugated to the 5′-end of each oligonucleotide to enable fluorescent detection.…”
Section: Materials and Methods Synthesis Of Oligonucleotidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to enhance tumor cell-specific binding or internalization of NPs with targeting agents like antibodies has been thoroughly investigated, [24,25] but only recently have researchers begun to examine the impact of these targeted NPs on downstream signaling events. [26,27] These studies are important because cell signaling manipulation by targeted nanoparticles is recognized as a promising therapeutic technique. [28] The rationale for using antibody-nanoparticle conjugates rather than freely delivered antibodies is supported by the fact that improvements in therapeutic efficacy have been observed for other molecules conjugated to or encapsulated within NPs, including peptides, [29] siRNAs or miRNAs, [30,31] chemotherapeutics, [3234] or a combination of these.…”
Section: Introductionmentioning
confidence: 99%